Taxonomic notes of the crazy ant (Hymenoptera: Formicidae: Paratrechina fulva) in Colombia - FERNÁNDEZ-C., FERNANDO (Revista Colombiana de Entomología, 2000)
The crazy ant Paratrechina fulva (Mayr) (Hymenoptera: Formicidae) was introduced in Colombia some decades ago for the control of poisonous snakes. The ant resulted in being one important plague for the man and their domestic animals. Due to the absence of a revision for the species of the genus in the Neotropical Region, taxonomic notes of the species are offered in order to help their identification. Paratrechina could be distinguished between other formicine for the stout and large hair (macrochaeta) in all its body except metanotum, propodeum, and petiole. and for their mandibular configuration, where the subbasal and intercalar teeth are the smallest. P. fulva could be distinguished in Colombia for their red-brown color and the dense pubescence in the thorax. giving a dull appearance to the ant.